Analysis of the approach run and the takeoff in the Japanese junior long jumpers - Omura, I.; Iiboshi, A.; Koyama, H.; Muraki, Y.; Ae, M. (ISB Congress, 2005)
The purpose of this study was to investigate the approach run of Japanese junior long jumpers to obtain the fundamental findings on effective approach run and the takeoff.